Neutrophil Extracellular Traps Go Viral - Schönrich, Günther; Raftery, Martin J. (Frontiers in Immunology, 2016)
Neutrophils are the most numerous immune cells. Their importance as a first line of defense against bacterial and fungal pathogens is well described. In contrast, the role of neutrophils in controlling viral infections is less clear. Bacterial and fungal pathogens can stimulate neutrophils to produce extracellular traps (NETs) in a process called NETosis. Although NETosis has previously been described as a special form of programmed cell, there are forms of NET production that do not end with the demise of neutrophils. As an end result of NETosis, genomic DNA complexed with microbicidal proteins is expelled from neutrophils. These structures can kill pathogens or at least prevent their local spread within host tissue. On the other hand disproportionate NET formation can cause local or systemic damage. Only recently was it recognized that viruses can also induce NETosis. In this review, we discuss the mechanisms by which NETs are produced in the context of viral infection and how this may contribute to both antiviral immunity and immunopathology. Finally, we shed light on viral immune evasion mechanisms targeting NETs.